2013
DOI: 10.1002/pbc.24491
|View full text |Cite
|
Sign up to set email alerts
|

PedsQL™ sickle cell disease module: Feasibility, reliability, and validity

Abstract: Background Sickle cell disease (SCD) is an inherited chronic disease that is characterized by complications such as recurrent painful vaso-occlusive events that require frequent hospitalizations and contribute to early mortality. The objective of the study was to report on the initial measurement properties of the new PedsQL™ SCD Module for pediatric patient self-report ages 5-18 years and parent proxy-report for ages 2-18 years. Procedure The 43-item PedsQL™ SCD Module was completed in a multisite study by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
131
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 126 publications
(141 citation statements)
references
References 50 publications
7
131
2
Order By: Relevance
“…29,30 The PedsQL sickle cell disease module, the only valid and reliable disease-specific measure for children with sickle cell disease, was also used. 31 HRQL assessments were measured at all 8 sites by paper report (parent proxy for all patients 18 years old or younger, self-report for patients 8 years old or older, and self-report with aid of the research coordinator for patients aged 5-7 years) before the first study drug infusion, after the sixth dose of medication (or immediately before discharge if fewer than 6 doses were administered), and by telephone 8 to 10 days postdischarge. Biomarkers were measured 1 hour after the fourth dose of medication and analyzed as previously described.…”
Section: Study Outcomesmentioning
confidence: 99%
“…29,30 The PedsQL sickle cell disease module, the only valid and reliable disease-specific measure for children with sickle cell disease, was also used. 31 HRQL assessments were measured at all 8 sites by paper report (parent proxy for all patients 18 years old or younger, self-report for patients 8 years old or older, and self-report with aid of the research coordinator for patients aged 5-7 years) before the first study drug infusion, after the sixth dose of medication (or immediately before discharge if fewer than 6 doses were administered), and by telephone 8 to 10 days postdischarge. Biomarkers were measured 1 hour after the fourth dose of medication and analyzed as previously described.…”
Section: Study Outcomesmentioning
confidence: 99%
“…Finally, the authors showed clinical potential and focusing the scale research of purposes to assess the severity of symptoms of fatigue [10] and said that the use of it will facilitate the understanding of health and wellbeing of children with the disease [9]. In Portugal, a version of PedsQL was also validated to be applied to children aged between 5-7 years old and 8-12 years old diagnosed with diabetes mellitus type 1 or spina bifida [8].…”
Section: Discussionmentioning
confidence: 99%
“…The synthesis build of the selected studies in the review show that the motivation to develop an instrument or quiz in the theme of chronical is strictly linked to factors, as: handling of a specific disease such as diabetes [6,7,8], sickle cell anemia [9,10], asthma [7,11,12], chronic kidney disease [13], Cystic fibrosis [14]; children and/or adolescents family inclusion in the validation process or as subject of the instrument application [6,10,15,16,17]; measurement of subjective dimensions of life experience with chronic disease such as: quality of life [7,13], satisfaction with care [17], chronic pain experience [18] as well as the limitations to develop common activities [19]. The use of statistical measures as tools to support the validity, reliability and reproducibility of instruments built was present in all studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations